Pengembangan Website Landing Page Prodi Informatika Universitas Pertahanan RI Menggunakan Metode Responsive Web Design - Amar Ma’ruf, Azzam; Savira, Jihan; Adrian Sitanggang, Johan; Aryaputra Piliang, Rizqullah; Jaya Gainal, Ido; Ahmad Firdaus, Eryan (LPPM Universitas Nias Raya, 2025)
The advancement of information technology requires educational institutions to provide effective communication media for delivering academic information to the public. A website plays a key role in this regard, serving as a digital gateway that reflects the institution’s credibility and professionalism. The Informatics Study Program at the Indonesian Defense University needs a landing page website that is not only informative and visually engaging but also accessible across a variety of devices and screen sizes. This study aims to design and develop a landing page using the Responsive Web Design (RWD) approach to ensure that the website display can dynamically adjust on desktops, tablets, and smartphones. RWD was chosen for its ability to deliver an optimal viewing experience through the use of flexible grid layouts, media queries, and responsive user interface elements. The development process also considered aspects of user interface (UI) and user experience (UX) to enhance user comfort and functionality. Testing results show that the website developed with the RWD method can effectively present information on various devices, support intuitive navigation, and improve overall accessibility. This website is expected to serve as a reliable communication medium and strengthen the professional image of the Informatics Study Program at the Indonesian Defense University in the digital space.